Maternal factors associated with fetal macrosomia in a public hospital of Lima - Peru, january to october 2018: Factores maternos asociados a macrosomía fetal en un hospital público de Lima - Perú, enero a octubre del 2018 - Bazalar Salas, Dania (2019)
Objective: To determine the maternal factors associated to fetal macrosomia in a Public Hospital of Lima - Peru, from January to October of 2018. Methods: Analytical, observational, retrospective study, of type cases and controls. A data collection form was used and for the statistical analysis the SPSS v25.0 program was used. Results: Of the 401 newborns, it was found that the weight gain during pregnancy 27.2% the mothers studied had an inadequate weight gain (OR=6.96, 95% CI4.22-11.48, p=0.00), regarding the prepregnancy weight category, and parity was 73 (73.7%). Also, maternal age was less than 35 years in 278 (92.1%), being statistically significant (p=0.004). Conclusion: It is concluded that there is a relationship of maternal factors such as inadequate weight gain during pregnancy, maternal pre-gestational weight, parity, maternal age associated with fetal macrosomia. DOI:10.25176/RFMH.v19.n2.2066